The Effect Of Using Special Visual Exercises In Learning Offensive Artistic Performance In Fencing For Learners With Hearing Impairment - Fadil, Abedulkareem; Fouad, Randa (Journal of Physical Education, 2018)
The Effect Of Using Special Visual Exercises In Learning Offensive Artistic Performance In Fencing For Learners With Hearing ImpairmentThe problem of the research lies in the lack of using teaching aids for fencers with disability especially those with hearing impairment who face difficulties in receiving information and dealing with others because they are deaf and dumb thus they heavily relay on sight. Thus the aim of the research using modern visual teaching aids to identify the effect of these exercises on learning offensive performance as well as identifying the effect of using ordinary exercises on learning offensive performance. The researchers used the experimental method on (6) students deaf and dumb from Al Amel institute. The subjects were divided into two groups then the teaching program was applied for 8 teaching sessions. The data was collected and treated using SPSS to conclude that both exercises led to the learning of offensive kills in fencing, in addition to that the experimental group learned better in both types of offensive artistic performance. Finally the researchers recommended using modern visual teaching aids in learning as well as paying attention to using modern teaching aids so as to make teaching more interesting.